Computational approach for predicting the adsorption properties and inhibition of some antiretroviral drugs on copper corrosion in HNO3 - Tigori, Mougo André; Kouyaté, Amadou; Kouakou, Victorien; Niamien, Paulin Marius; Trokourey, Albert (European Journal of Chemistry, 2020)
The use of computational chemistry as an effective means of designing eco-friendly organic corrosion inhibitors has been greatly enhanced by the development of Density Functional Theory (DFT). In this study, the inhibitory activity of four antiretroviral drugs, namely, lamivudine, emtricitabine, didanosine and stavudine, was analyzed by this theory. The quantum chemical parameters/descriptors calculated using DFT at B3LYP/6-31G(d) level were used to explain the mechanism of electron transfer between the inhibitors and the copper surface. The results showed that these compounds adsorb on copper surface. It is important to consider the effect of films formed by the adsorption products. In addition, the Fukui functions and the dual descriptor were used as indicators to locate the electrophilic and nucleophilic attack sites within each compound. Finally, the DFT has enabled to accurately predict the adsorption properties and the good inhibition performance of the molecules in the solution studied.